Ответ(ы) на вопрос:
решение смотри в приложении
1
ОДЗ x>0
log(2)x=a
(3a+2)/(a²+a-2)+1<0
(3a+2+a²+a-2)/(a²+a-2)<0
(a²+4a)/(a²+a-2)<0
a²+4a=0⇒a(a+4)=0⇒a=0 U a=-4
a²+a-2=0
a1+a2=-1 U a1*a2=-2⇒a1=-2 U a2=1
+ _ + _ +
-------------(-4)--------------(-2)-----------------(0)-----------(1)-----------------
-40
log(3)x=a
(a²+4a-1)/(a+3)(a+1)-1/(a+1)≤0
a²+4a+3=0⇒a1+a2=-4 U a1*a2=3⇒a1=-3 U a2=-1
(a²+4a-1-a-3)/(a+3)(a+1)≤0
(a²+3a-4)/(a+3)(a+1)≤0
a²+3a-4=0⇒a1+a2=-3 U a1*a2=-4⇒a1=-4 U a2=1
+ _ + _ +
----------------[-4]---------------(-3)------------(-1)------------[1]-----------------
-4≤a<-3⇒-4≤log(3)x<-3⇒1/81≤x<1/27
-1-5
{a²-3a-2<2
a²-3a-2+5>0
a²-3a+3>0
D=9-12=-3<0⇒a∈R
a²-3a-2<2
a²-3a-4<0
a1+a2=3 U a1*a2=-4⇒a1=-1 U a2=4
-1
Не нашли ответ?
Похожие вопросы